Role of long non-coding RNAs in rice reproductive development - Babaei, Saeid; Singh, Mohan B.; Bhalla, Prem L. (Frontiers in Plant Science, 2022)
Rice is a staple crop, feeding over half of the global population. The future demand of population growth and climate change requires substantial rice improvement. Recent advances in rice genomics have highlighted the vital role of the non-coding part of the genome. The protein-coding regions account for only a tiny portion of the eukaryotic genome, and most of the genomic regions transcribe copious amounts of non-coding RNAs. Of these, the long non-coding RNAs, including linear non-coding RNAs (lncRNAs) and circular non-coding RNAs (circRNAs), have been shown to play critical roles in various developmental processes by regulating the expression of genes and functions of proteins at transcriptional, post-transcriptional and post-translational levels. With the advances in next-generation sequencing technologies, a substantial number of long non-coding RNAs have been found to be expressed in plant reproductive organs in a cell- and tissue-specific manner suggesting their reproductive development-related functions. Accumulating evidence points towards the critical role of these non-coding RNAs in flowering, anther, and pollen development, ovule and seed development and photoperiod and temperature regulation of male fertility. In this mini review, we provide a brief overview of the role of the linear and circular long non-coding RNAs in rice reproductive development and control of fertility and crop yield.